Valor diagnóstico e prognóstico da angiotomografia das coronárias na emergência : overview com meta-análise de revisões sistemáticas - Tavares, Irlaneide da Silva (2016)
The evaluation of acute chest pain in the emergency department is time-consuming, costly, it is associated with a prolonged length of stay and not rarely the diagnosis is overlooked. The aim of this report was to conduct an overview with meta-analysis to compile evidence from multiple systematic reviews (SRs) related to diagnostic value and prognostic of coronary computed tomography angiography (CCTA) in the assessment of acute chest pain in the emergency departments (ED). We included SRs of primary studies that evaluated the diagnostic value and prognostic of CCTA ≥ 64 channels in the ED. The studies were conducted in patients with low and intermediate risk of CAD with normal cardiac enzymes and nonischemic initial ECG. The quality assessment was performed using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) and approved revisions that obtained score ≥ 80%. Two authors independently extracted data using a standardized form. Numerical variables were described as mean and standard deviation and categorical as simple and relative frequencies. We use Spearman correlation test, Chi-square test, Cochran’s Q test or Higgins and Thompson statistical I2. For meta-analysis was used "mada" packet (R Core Team, 2015). Four reviews were eligible for inclusion in this overview, resulting in 13 articles after the criteria of exclusion and only 10 of these were used for meta-analysis. A total of 4831 patients, with a mean age of 54 ± 6 years, 51% male, 46% were hypertensive, 32% had dyslipidemia, 13% diabetes and 26% with family history CAD premature. In the meta-analysis, nine studies defined CCTA positive when presented luminal lesions ≥ 50% and one study ≥ 70%. The sensitivity ranges from 77% to 98% and the specificity ranges from 73% to 100%. The univariate analysis showed homogeneity of DOR [Q = 8.5 (df = 9), p = 0.48 and I2 = 0%]. The pooled mean DOR for CCTA in primary analyses was 4.33 (95% CI: 3.47 - 5.18). The area under the curve (AUC) = 0.982 (95% CI: 0.967 - 0.999). There were no deaths, 29 (0.6%) infarcts, 92 (1.9%) revascularizations and 312 (6.4%) invasive coronary angiography. The diagnosis of ACS occurred in 7.3% of 1655 patients included in the meta-analysis. The use of CCTA as a tool for stratification of patients with cardiovascular risk low or intermediate, which are in the emergency room with chest pain, has high accuracy, safety, reduces length of hospital stay and probably the costs, producing an early diagnosis and more effective in decision making. To assess the value of CCTA in the prevention of future events, studies with more appropriate design and longer follow-up are necessary.